Implementation of Differentiated Learning on Mathematical Critical Thinking Ability - Irma Surya Afriani; Irwani Zawawi; Syaiful Huda (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research focuses on the differences in mathematical critical thinking skills between students who use differentiated learning strategies and those who use undifferentiated learning strategies. The methodology used in this research is experimental research using the nonequivalent posttest-only control group design. The participants of this study consisted of X-1 and X-3 students at SMA Negeri 1 Mantup with 30 students in each class. Each class was divided into 5 groups with the number of each group of 6 students. The data used in this study came from instruments in the form of a questionnaire that assessed students' learning styles in the experimental class, as well as a post-test that measured mathematical critical thinking skills. The posttest used consists of three essay questions covering 4 critical thinking indicators, namely interpreting, analyzing, evaluating, and inferring. The scores obtained by students will be assessed using the T test or independent samples T test. Based on the research findings, 3 learning style groups were obtained with 14 students of visual learning style, 8 students of auditorial learning style, and 8 students of kinesthetic learning style, respectively. For the post-test results of each class showed that there were differences in mathematical critical thinking skills between students who received differentiated learning and students who received undifferentiated learning with a t value of 2.781 exceeding the t table value of 2.001 which means there is an influence between differentiated learning on mathematical critical thinking skills.